Online Gaming Regulation A Tussle between the Union and States - Ayushi Raghuvanshi (Mumbai EPW, 2024)
Online gaming and online fantasy sports platforms have experienced tremendous growth and popularity as a result of increasing internet penetration, affordable smartphones.Online gaming can be regulated by the union through legislation under entry 31 of the union list in the seventh schedule of the Constitution At present there is no central statute on online gaming in India except the Public Gaming Act 1867 and the recently pass amendment in the IT rules 2021 which provide certain regulations for online real money gaming. Some states have banned online gaming together The government has yet to provide an answer to how their interest would be safeguarded against state actions. The state action need to be studied understand the approach other states have towards online gaming and how the approach is contradictory.
Keywords: Online Gaming; Gaming Industry; Stakeholders; Regulations